ANALYSIS OF PROPERTIES OF CONCRETE USING POTASSIUM POWDER AS ADMIXTURE - Gadgihalli, Vishal; Ramya; Khan, Abrar; Dinakar, Raghavendra Prasad (International Journal of Research -GRANTHAALAYAH, 2017)
Chemical admixtures are the ingredients in concrete other than Portland cement, water and aggregate those are added to mix immediately before or during mixing. These admixtures are primarily used to reduce the cost of concrete construction, to modify the properties of hardened concrete, to ensure the quality of concrete during mixing, transportation, placing curing and to overcome certain emergences during concrete operations. In this paper analysis of properties of concrete using potassium power as admixture is studied and verified the strength of concrete and temperature emitted due to chemical reaction to normal Portland cement. Using potassium powder the temperature emitted due to exothermal reaction of concrete has reduced. Thus gives better results hence we can use this potassium powder as an admixture where the temperature and the emitting temperatures place a crucial role in construction and maintenance.